Interação de troca magnética em tricamadas do tipo Fe/Mn/Co crescidas por feixe molecular : caracterização estrutural e magnética - Freitas, Tales Costa de (2013)
MgO(001)/Cr/Ag/Fe/Mn(t)/Co/Si type films were epitaxially grown by MBE to study the coupling angle behavior of the bcc-Fe-and bcc-Co layers separated by the Mnbcc metastable phase (bcc – body centered cubic). It was investigated the influence of the epitaxial growth of the layers and their interfacial roughnesses (structural and / or chemical), induced by change Mn thickness, on the exchange coupling angle using reflection high energy electron diffraction, X-ray reflectivity (diffraction on low angles - 2? < 10 °) and Mössbauer spectroscopy of conversion electrons (1nm thick layer of 57Fe deposited at the interface Fe/Mn). Volumetric magnetic properties, which can give us the coupling angle behavior, were studied by vibrating sample magnetometry (VSM) and ferromagnetic resonance (FMR). For the set of studied samples, it was observed that all layers were epitaxially grown, except in case of Co where we could not get the results. It was particularly found that Mn layer can grow epitaxially for thicknesses smaller than 1.16 nm. For greater Mn thicknesses, it may be continued epitaxially or a phase transition occurs (transition from Mn-ccc to a –Mn phase). Furthermore, we noted that there is an enhancement of the Mn roughness with the increase of its thickness (a result seen by a reduction of RHEED signal intensity and from the fittings of the reflectivity curves). Mössbauer spectroscopy has mainly shown a presence of two fractions: one contribution which is not affected by the interface (with a-Fe properties) and other one, which is directly affected by the Fe/Mn interface and measured by a reduction in Fe coordination numbers and/or Mn neighborhood. For both fractions, the Fe magnetic moments are in the film plane, as measured by the ratio of the spectra I23 intensity, which reach a value close to 4. From FMR and VSM data, it was found that Fe-bcc and Co-bcc layers have a non collinear coupling for all samples; an effect that is associated with changes on Mn thickness as well on interfacial roughness. It was also determined the magnetic anisotropies of the Fe-bcc and Co-bcc layers; Co anisotropy is 10% bigger than the Fe one in the studied trilayers. Overall, our results indicate that the roughness on the Fe/Mn interface is nearly constant, affecting 0.4 nm of the 1nm thick 57Fe layer deposited at this interface, but now specific results were obtained on the Mn/Co interfaces. Therefore, the observed coupling angle fluctuations still need further investigations, since it cannot be purely attributed to the magnetic spring effect from the Mn antiferromagnetic phase.